2004
DOI: 10.1210/en.2003-1174
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Testicular Steroidogenesis by the Xenoestrogen Bisphenol A Is Associated with Reduced Pituitary Luteinizing Hormone Secretion and Decreased Steroidogenic Enzyme Gene Expression in Rat Leydig Cells

Abstract: Exposure of humans to bisphenol A (BPA), a monomer in polycarbonate plastics and a constituent of resins used in food packaging and dentistry, is significant. In this report exposure of rats to 2.4 microg/kg.d (a dose that approximates BPA levels in the environment) from postnatal d 21-35 suppressed serum LH (0.21 +/- 0.05 ng/ml; vs. control, 0.52 +/- 0.04; P < 0.01) and testosterone (T) levels (1.62 +/- 0.16 ng/ml; vs. control, 2.52 +/- 0.21; P < 0.05), in association with decreased LHbeta and increased estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
284
4
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(319 citation statements)
references
References 67 publications
26
284
4
5
Order By: Relevance
“…There is now growing evidence showing endocrine-disrupting effects of BPA at doses lower than the reference limits (11,12,31,32). The present dose-response study on intestinal permeability shows a half-maximal inhibitory dose for BPA 10 fold below the TDI.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…There is now growing evidence showing endocrine-disrupting effects of BPA at doses lower than the reference limits (11,12,31,32). The present dose-response study on intestinal permeability shows a half-maximal inhibitory dose for BPA 10 fold below the TDI.…”
Section: Discussionmentioning
confidence: 48%
“…However, recent studies revealed that chronic exposure to these reference doses alters some biological endpoints (8,9), warranting a request for reevaluation of human safe daily intake limits (4,10). To date, most studies examining the estrogenic impact of BPA have focused on reproductive function (11)(12)(13) and, more recently, on brain development (14,15). In contrast, although the gut is in direct contact with orally absorbed BPA, the endocrine impact on the intestinal barrier function remains an unexplored endpoint.…”
mentioning
confidence: 99%
“…Presence of BPA in the human endometrium [26] supports the idea that there may be possible interactions between BPA and endogenous estrogen in the local environment. Complex role of BPA in testicular steroidogenesis is also reported recently [27].…”
Section: Discussionmentioning
confidence: 76%
“…The details of the primers used, number of cycles, and size of the PCRamplified products are listed in Table 1. The primers used for RT-PCR for StAR protein and cytochrome P 450 scc were gene-specific primers selected according to Akingbemi et al (2004). The 3b-HSD type I and 17b-HSD type III were selected according to Sakaue et al (2002).Ten microliters of each PCR product were analyzed by gel electrophoresis on a 2% agarose gel.…”
Section: Rt-pcrmentioning
confidence: 99%